Production and Comprehension of Pantomimes Used to Depict Objects - van Nispen, Karin; van de Sandt-Koenderman, W. Mieke. E.; Krahmer, Emiel (Frontiers in Psychology, 2017)
Pantomime, gesture in absence of speech, has no conventional meaning. Nevertheless, individuals seem to be able to produce pantomimes and derive meaning from pantomimes. A number of studies has addressed the use of co-speech gesture, but little is known on pantomime. Therefore, the question of how people construct and understand pantomimes arises in gesture research. To determine how people use pantomimes, we asked participants to depict a set of objects using pantomimes only. We annotated what representation techniques people produced. Furthermore, using judgment tasks, we assessed the pantomimes' comprehensibility. Analyses showed that similar techniques were used to depict objects across individuals. Objects with a default depiction method were better comprehended than objects for which there was no such default. More specifically, tools and objects depicted using a handling technique were better understood. The open-answer experiment showed low interpretation accuracy. Conversely, the forced-choice experiment showed ceiling effects. These results suggest that across individuals, similar strategies are deployed to produce pantomime, with the handling technique as the apparent preference. This might indicate that the production of pantomimes is based on mental representations which are intrinsically similar. Furthermore, pantomime conveys semantically rich, but ambiguous, information, and its interpretation is much dependent on context. This pantomime database is available online: https://dataverse.nl/dataset.xhtml?persistentId=hdl:10411/QZHO6M. This can be used as a baseline with which we can compare clinical groups.